Bioinformatics-based analysis of nicotinamide adenine dinucleotide metabolism-related genes to predict immune status and prognosis for head and neck squamous cell carcinoma patients - Guan, Zhenjie; Gu, Xinyu; Zheng, Lian (Frontiers in Immunology, 2025)
BackgroundPatients suffering from head and neck squamous cell carcinoma (HNSCC) have a high recurrence rate and poor prognosis. Nicotinamide adenine dinucleotide (NAD+) is crucial in the progression of the tumor. Currently, the specific role of NAD+ in HNSCC remains elusive.MethodsFirst, weighted gene co-expression network analysis (WGCNA) was utilized to screen gene modules linked to NAD+ metabolism-related genes (NMRGs), and the expression profiles obtained were taken as intersections with differentially expressed genes (DEGs) between HNSCC and control samples. The genes were further compressed and risk modeled using LASSO and stepwise regression analyses. Then the gene mutation landscapes of different risk subgroups of HNSCC were analyzed using MuTect 2 software. Differences in biological function and immune infiltration analyses between different subgroups were explored. In addition, scratch and transwell assays were carried out to explore the role of PSME1 in HNSCC cells.ResultsHere, we screened two specific modules with the strongest relation to HNSCC by WGCNA and subsequently took the intersection of 6160 DEGs with the module genes, obtaining a total of 359 intersected genes. 6 (ICOS, PSME1, SERPINA1, SH3KBP1, SP100 and ZAP70) characterized genes linked to HNSCC prognosis were selected for risk modeling. We categorized patients by the risk scores into high- and low-risk groups. Overall survival (OS) of patients in the low-risk group was significantly better than those in the high-risk group. Compared to the low-risk group, the mutation rates of FAT1, TP53, TTN genes were higher in the high-risk group, with a coexistence between the mutated genes. The expression of the characterized genes showed a positive association with the level immune cell infiltration, for example, activated CD8 T cells. The enrichment analysis demonstrated that differential genes in the high-risk HNSCC group were significantly enriched in the ribosome and other pathways, while the differential genes in the low-risk group were mainly involved in arachidonic acid metabolism and other pathways. Further in vitro assay revealed that downregulated PSME1 attenuated the migratory and invasive abilities of FaDu cells.ConclusionsThe current work provided theoretical references for future study on potential biomarkers of prognosis and immune infiltration in patients suffering from HNSCC.